Spin-1/2 Ising model on a AFM/FM two-layer Bethe lattice in a staggered magnetic field - KPLE, JOËL; MASSOU, SIAKA; HONTINFINDE, FÉLIX; ALBAYRAK, Erhan (My University, 2018)
A bilayer spin-1/2 Ising model consisting of two superposed Bethe lattices with antiferromagnetic/ferromagnetic interactions is studied by the use of exact recursion relations in a pairwise approach in the presence of an external staggered magnetic field. Besides the ground state phase diagrams calculated in different possible planes of the model parameters space, the thermal variations of the order-parameters and the free energy are investigated to obtain the temperature-dependent phase diagrams of the model for different values of the coordination numbers q. Our calculations reveal that depending on the strength of the model parameters, the model exhibits a variety of interesting phase transitions and therefore phase diagrams.
Keywords: Phase transitions; Spin-1/2 Ising model; Bilayer Bethe lattice; Ground states phase diagrams; Exact recursion relations; Second-order phase boundaries